Case Report: From behavioral disorder to surgical emergency: a case of intussusception due to pica in an adolescent - Alhaj, Mohammed A.; Ahmed, Mohamed Hassan; Jalkhi, Tala; Armouche, Rama; Alrushdi, Mira Amer; Elmaghraby, Hania (Frontiers in Psychiatry, 2025)
BackgroundPica is a complex behavioral condition with both psychological and biological components, characterized by the persistent ingestion of non-nutritive substances. It often coexists with other mental health conditions, and when left untreated, may lead to life-threatening medical complications. While gastrointestinal obstruction is a known outcome, intussusception caused by pica is extremely rare, particularly in adolescents.Case presentationWe report a case of a 13-year-old Middle Eastern girl of mixed Emirati Indonesian descent, with a history of emotional distress and familial instability, who presented with persistent abdominal pain and vomiting. Imaging revealed an intussusception caused by foreign bodies extending from the stomach to the duodenum. The patient underwent emergency laparotomy, during which multiple ingested objects were removed, including hair ties, shoelaces, and a thin metal wire. A postoperative psychiatric evaluation led to a diagnosis of pica and major depressive disorder. Cognitive Behavioral Therapy (CBT) was initiated shortly after diagnosis, and the patient demonstrated significant clinical improvement, including cessation of pica behaviors without pharmacological intervention.ConclusionThis case demonstrates the rarity of intussusception as a surgical complication of pica and highlights the importance of early psychiatric assessment and coordinated multidisciplinary care. The patient’s recovery was facilitated by timely psychosocial intervention, with marked improvement following the introduction of CBT.